Design of a Light-Weight Vertical Tail for a Hybrid High-Altitude Pseudo-Satellite - Feliciano Di Biase; Domenico Varricchio; Vincenzo Rosario Baraniello; Giuseppe Persechino (Engineering Proceedings)
The interest in high-altitude pseudo-satellites (HAPSs) has significantly increased in recent years due to the great versatility of these platforms, which allows them to be employed in a wide variety of applications in civilian and military fields. This study focuses on the design of an innovative hybrid airship vertical tail. The empennage proposed is internally sustained with a light-weight structure and coated with a thin film, avoiding any leakage that would occur with inflated structural elements. The design of the vertical tail and its structural analysis through a detailed finite element (FE) model are presented to show its overall behavior subjected to the aerodynamic loads.